Urseodeoxycholic acid thrapy in gallstone disease - Selim Giray NAK,; Altay TÜRKSÖZ,; Macit GÜLTEN,; Selim GÜREL,; Yusuf KARAARSLAN,; Enver DOLAR,; Faruk MEMİK, (Turkish Journal of Gastroenterology, 2019)
-